Access to β‐Lactams by Enantioselective Palladium(0)‐Catalyzed C(sp3)H Alkylation1. (1st July 2014) - Pedroni, Julia; Boghi, Michele; Saget, Tanguy; Cramer, Nicolai
Abstract β‐Lactams are very important structural motifs because of their broad biological activities as well as their propensity to engage in ring‐opening reactions. Transition‐metal‐catalyzed CH functionalizations have emerged as strategy enabling yet uncommon highly efficient disconnections. In contrast to the significant progress of Pd0‐catalyzed CH functionalization for aryl–aryl couplings, related reactions involving the formation of saturated C(sp3)C(sp3) bonds are elusive. Reported here is an asymmetric CH functionalization approach to β‐lactams using readily accessible chloroacetamide substrates. Important aspects of this transformation are challenging C(sp3)C(sp3) and strain‐building reductive eliminations to for the four‐membered ring. In general, the β‐lactams are formed in excellent yields and enantioselectivities using a bulky taddol phosphoramidite ligand in combination with adamantyl carboxylic acid as cocatalyst.